Rewilding life together: Bonhoeffer, spirituality, and interspecies community. Issue 2 (1st July 2022) - Dahill, Lisa E.
Abstract: In a time of grave ecological danger, compounding injustices, and resource stresses threatening entire human and ecosystemic populations, we need new forms of life together, an intentional interspecies weirding of inherited religious visions of community. The recent turn toward place‐based thinking orients our gaze back to the actual places we live, learning again to see, love, and sustain relationships with their creatures and elements. This article stands within that larger development of place‐based hermeneutics: engaging Dietrich Bonhoeffer's Life Together toward an interspecies broadening of what Christian community means. Such life together takes distinctive shape in each particular place: here, the fire‐charred chaparral and car‐centered built world of southern California, haunted by European settlers' annihilation of the local indigenous humans, grizzlies, and groundwater, ground zero now for climate‐, pandemic‐, extinction‐, and immigrationjustice challenges. The article's process generates new insights in the study of Bonhoeffer's legacy and hermeneutical strategies useful for other projects in place‐based (re‐) readings of classic texts in Christian spirituality.